Sposoby odżywiania się przez konsumentów – nowe trendy - Dejnaka, Agnieszka (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Food trends are developing and are likely to develop in two extreme directions. A few years ago, superfoods products were difficult to access, today they are everyday life on store shelves. It is difficult to determine how many trends are currently on the market regarding the ways of consuming consumers, however, there are a lot of them and from day to day new “ideas for nutrition” are coming. The chapter presents selected new trends regarding the way consumers eat. Selected food trends of consumers were described: “conscious nutrition”, “respect for animals” and “being fit”. The aim of the chapter was to evaluate new trends in consumer nutrition. The goal was achieved through literature studies, presentation and analysis of secondary research results and their interpretation and based on critical analysis of tren
Keywords: nutrition trends; conscious nutrition; fit; consumer behavior